2018
DOI: 10.21274/ls.2018.10.1.61-80
|View full text |Cite
|
Sign up to set email alerts
|

Genre - Based Approach for Writing Recount Text at MTs "Darul Ulum" Karang Pandan, Pasuruan

Abstract: Among other skills, writing is often seen as a difficult skill for English as a Foreign Language (EFL) learners. In particular, writing seems to be a difficult subject for the students of MTs.Darul Karangpandan Pasuruan. It could be seen from the result of the preliminary study, which showed that the ability of the eight grade students of MTs. Darul Ulum Karangpandan in writing paragraphs was still poor. This research was aimed at improving the students' ability in writing recount text through Genre-Based Appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
4
5
0
Order By: Relevance
“…These findings are in line with previous studies that reported SFL GP could be used to teach the students' skills in writing procedural types (Istianah, 2011), in writing narrative texts (Zurdianto, 2016) and recount texts (Hidayat et al, 2018), and to build the senior high school students' character values by using narrative texts (Hardini, 2013). Unlike the previous studies, this study not only used SFL GP teaching procedures and principles but also added a rewriting strategy, a form of a Reading to Learn teaching strategy or procedure, to help the students in constructing their texts.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are in line with previous studies that reported SFL GP could be used to teach the students' skills in writing procedural types (Istianah, 2011), in writing narrative texts (Zurdianto, 2016) and recount texts (Hidayat et al, 2018), and to build the senior high school students' character values by using narrative texts (Hardini, 2013). Unlike the previous studies, this study not only used SFL GP teaching procedures and principles but also added a rewriting strategy, a form of a Reading to Learn teaching strategy or procedure, to help the students in constructing their texts.…”
Section: Discussionsupporting
confidence: 90%
“…One of the writing text Genre and Language function should be taught Recount text. [3] stated that recount text is to list and describe past experiences by retelling events in which they happened (chronological order). This recount text aims to provide the audience with information about what and when it occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The first element of SFL GP is texts (Derewianka, 2015;Nagao, 2019;Rose & Martin, 2014). Many studies had used SFL GP in the context of secondary level of education for teaching written texts such as descriptive (Ahmad, 2018;Nahid et al, 2018), narrative (Zurdianto, 2016), and recount texts (Hidayat et al, 2018). Unlike the earlier studies, this study used simple spoken texts to help build the YELs' capacities in communicating in a spoken manner by using English.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SFL GP had been used in many countries, including in Indonesia, in formal contexts at the secondary level of education to teach various written genres or text types, such as recount texts (Hidayat et al, 2018), descriptive texts (Ahmad, 2018;Nahid et al, 2018), and narrative texts (Zurdianto, 2016). At the tertiary level of education, studies have used SFL GP to teach academic writing (Emilia & Hamied, 2015;Haerazi & Irawan, 2019;Nagao, 2019).…”
Section: Indonesian Journal Of English Languagementioning
confidence: 99%